Continuous Flow Composite Membrane Catalysts for Efficient Decomposition of Chemical Warfare Agent Simulants - Seo, Jin Young; Cho, Kie Yong; Lee, Jung-Hyun; Lee, Min Wook; Baek, Kyung-Youl (American Chemical Society, 2020)
Continuous and safe decomposition of chemical warfare agents (CWAs) is a critical requirement to protect both soldiers and citizens and to eliminate the stockpiles after the cold war. The Zr-based metal-organic framework (Zr-MOF) has been known as the most effective catalyst for decomposing CWAs, especially the most fatal nerve agents, however, its low processability due to the powder form limits its expansion to actual military applications. To this end, the composite membrane catalysts (CMCs) comprising the Zr-MOF (UiO-66 catalyst) and nylon 6 nanofiber (porous supporter) are developed by the simple integration of electrospray and electrospinning, resulting in selective immobilization of UiO-66 on the surface of the nylon 6 nanofibers. These strategical benefits of CMCs gave super catalytic durability including recyclability over five times without decreasing the catalytic activity for the decomposition of methyl paraoxon (MPO), a simulant of the nerve agent, in the presence of N-ethylmorpholine (N-EM), which was not achieved in the original particulate UiO-66. Because of the excellent physical and chemical stabilities of CMCs, the CMC with 56 wt % of UiO-66 (CMC56) decomposed 198 g of MPO within an hour in the continuous flow system with a flow rate of 21.6 mL h(-1). This study highlights the important strategies in designing the feasible membrane-type catalysts with superior catalytic activity and robust durability for decomposing CWAs in the continuous flow system.
Keywords: ORGANIC-FRAMEWORK COMPOSITES; PHOTOCATALYTIC OXIDATION; NANOFIBER MATS; DEGRADATION; HYDROLYSIS; ORGANOPHOSPHORUS; UIO-66; NANOPARTICLES; PROTECTION; SUSPENSION